2018
DOI: 10.3390/ijms19123996
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of CUB and Sushi Multiple Domains 1 Inactivation in Head and Neck Squamous Cell Carcinoma

Abstract: Although the genetic alteration of CUB and Sushi multiple domains 1 (CSMD1) is known to be associated with poor prognosis in several cancers, there is a lack of clinical relevance in head and neck cancer. The aim of this study was to offer insight into the clinical significance of CSMD1, utilizing a multimodal approach that leverages publicly available independent genome-wide expression datasets. CSMD1-related genes were found and analyzed to examine the clinical significance of CSMD1 inactivation in the HNSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Multiple mechanisms can reduce the expression of CSMD1. The allelic loss, mutation and methylation of CSMD1 have been detected in breast cancer, head and neck cancer, oral squamous cell carcinoma, prostate cancer, rectum, liver, lung and skin cancer and many other malignant tumors such as breast cancer, head and neck cancer, oral squamous cell carcinoma, prostate, colorectal cancer, liver cancer, lung cancer and skin cancer, etc [5,6,[8][9][10][11][12][13][14][15][16]. Using four databases of TargetScan, Miranda, miRWalk and PicTar, highly conserved microRNA-10b binding sites were found in CSMD1 3′-UTRs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple mechanisms can reduce the expression of CSMD1. The allelic loss, mutation and methylation of CSMD1 have been detected in breast cancer, head and neck cancer, oral squamous cell carcinoma, prostate cancer, rectum, liver, lung and skin cancer and many other malignant tumors such as breast cancer, head and neck cancer, oral squamous cell carcinoma, prostate, colorectal cancer, liver cancer, lung cancer and skin cancer, etc [5,6,[8][9][10][11][12][13][14][15][16]. Using four databases of TargetScan, Miranda, miRWalk and PicTar, highly conserved microRNA-10b binding sites were found in CSMD1 3′-UTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Hunman CUB and sushi multiple domains protein 1 (CSMD1) is a novel candidate tumor suppressor gene located on the p arm of chromosome 8 (8p23) [4]. Previous studies have shown that the deletion of 8p23.2 or reduced expression of CSMD1 has something to do with poor prognosis in many cancers [5][6][7][8][9]. Multiple mechanisms can reduce the expression of CSMD1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While UNC13C and STEAP4 mutations have been found human head and neck cancers, their role in oral carcinogenesis remains unclear. Similarly, deletion of CSMD1 gene has been associated with lymph node metastasis and poor prognosis in several cancers and is seen commonly in smokers [35]. We detected the less common NOTCH2 mutation in RP-MOC1 cells.…”
Section: Discussionmentioning
confidence: 58%
“…Recurrent SVs in CSMD1, WWOX, ERC1, PDE4D and SHANK2 were also identified in five tumor samples. The CUB and Sushi multiple domains 1 (CSMD1) is a tumor suppressor gene reported to be associated with poor prognosis in many cancer types including breast cancer, gastric cancer, head and neck squamous cell carcinoma (HNSCC), and hepatocellular carcinoma (Deng et al, 2012) , (Zhang et al, 2019) , (Jung et al, 2018). Deletion of WWOX, a tumor suppressor gene, is frequent in esophageal adenocarcinoma (32%) and stomach adenocarcinoma (30.2%) and also observed in other human cancer types such as colon adenocarcinoma, bladder urothelial carcinoma and lung adenocarcinoma (Hussain et al, 2019).…”
Section: Structural Variations In Esccmentioning
confidence: 99%